Effects of astaxanthin and emodin on the growth, stress resistance and disease resistance of yellow catfish (Pelteobagrus fulvidraco). (April 2016) - Liu, Fei; Shi, Hong-zhuan; Guo, Qiao-sheng; Yu, Ye-bing; Wang, Ai-ming; Lv, Fu; Shen, Wen-biao
Abstract: Yellow catfish ( Pelteobagrus fulvidraco ) has become a commercially important fish species in China and eastern Asia. High-density aquaculture has led to congestion and excessive stress and contributed to bacterial infection outbreaks that have caused high mortality. We investigated the effects of dietary supplementation with astaxanthin and emodin alone and in combination on the growth and stress resistance of yellow catfish. After 60 days of feeding, each group of fish (control, astaxanthin, emodin, and astaxanthin plus emodin (combination) groups) was exposed to acute crowding stress for 24 h, and a subsample of fish from the four groups was challenged with the bacterial septicemia pathogen Proteus mirabilis after the end of the crowding stress experiment. Compared with the control, the astaxanthin and emodin groups showed increases in serum total protein (TP), hepatic superoxide dismutase (SOD) activity and hepatic heat shock proteins 70 (HSP70) mRNA levels at 12 and 24 h after the initiation of crowding stress. The combination group exhibited increases in alanine aminotransferase (ALT) activity, aspartate aminotransferase (AST) activity, serum TP, hepatic SOD activity and hepatic HSP70 mRNA levels within 24 h after the initiation of crowding stress. However, decreases relative to the control were observed in the serum cortisol and glucose contents in the three treatment groups at 12 and 24 h after the initiation of crowding stress, in ALT and AST activity in the astaxanthin and emodin group at 24 h after the initiation of crowding stress, and in the serum lysozyme activity, serum alkaline phosphatase (ALP) activity, and hepatic catalase (CAT) and malondialdehyde (MDA) activity in the combination group at 24 h after the initiation of crowding stress. Additionally, the cumulative mortality after P. mirabilis infection was lower in all three treatment groups (57.00%–70.33%) than in the control (77.67%). Dietary supplementation with astaxanthin and emodin decreased the specific growth rate (SGR) and weight gain (WG) of healthy yellow catfish, although significant differences in mortality were not observed. These results indicate that dietary supplementation with 80 mg/kg astaxanthin and 150 mg/kg emodin can improve the anti-oxidative capabilities, hepatic HSP70 levels, and resistance to acute crowding stress of yellow catfish. Finally, an appropriate strategy for enhance yellow catfish stress resistance and disease resistance is proposed. Highlights: Astaxanthin and emodin increase the stress resistance and immunity of fish. Astaxanthin and emodin can affect the expression of HSP70 in fish. Astaxanthin and emodin synergistically enhance immunity in fish.